Aliovalent Calcium Substitution: An Effective Way to Enhance the Magnetoelectric Coupling Properties of Multiferroic BiFeO3. Issue 24 (28th November 2022) - Mohan, Manoj; Al-Omari, Imaddin A.; Al-Harthi, Salim H.; Myint, Myo T. Z.; Jacob, Bibin; Dhanyaprabha, K. C.; Thomas, Hysen
Abstract : Kinetics of magnetoelectric coupling in bismuth ferrite (BiFeO3 ) with the substitution of aliovalent calcium ion is investigated. The resulting structural, dielectric, magnetic, and magnetoelectric (ME) coupling properties are explained in terms of chemical pressure originating from the substituent ion. Substitution of calcium finds to reduce the oxygen vacancies. Two important substitution concentrations find to be critical in ferroelectric (FE) and ME coupling properties. At 10 at% calcium, highest remanent polarization is obtained and maximum ME coupling coefficient is observed at 20 at%, which suggests calcium concentration between 10% and 20% can be optimized to obtain good electrical and ME coupling properties of BiFeO3 . Maximum ME coupling coefficient at calcium concentration 20 at% is close to numerical calculations reported in the literature. Magnetic properties are also favorably modified by the substitution; a coupled antiferromagnetic and weak ferromagnetic ordering is obtained. Also, a variation in blocking temperature and spin relaxation is observed with respect to the substituent ion concentration. Abstract : Substitution of Ca at the A‐site of multiferroic perovskite oxide bismuth ferrite (Bi1− x Ca x FeO3 ) is experimented through facile citrate gel autocombustion method. The compositions are studied for its structural, electrical, magnetic and magnetoelectric (ME) coupling properties with the variation in calcium concentration. The maximum ME coupling is obtained for a composition with 20 at% calcium substitution.